Stability of Neel Skyrmions in Ultra-Thin Nanodots Considering Dzyaloshinskii-Moriya and Dipolar Interactions - Escrig-Murua, J; Riveros-Rodriguez, A; Vidal-Silva, N (Elsevier B.V., 2017)
An analytical expression for the energy of Neel skyrmions in ultra-thin nanodots considering exchange, uniaxial anisotropy, Dzyaloshinskii-Moriya, and dipolar contributions has been obtained. In particular, we have proposed for the Neel skyrmion, a general ansatz for the magnetization component perpendicular to the dot, given by mz(r)=[1-(r/Rs)n]/[1+(r/Rs)n], where Rs is the radius of the skyrmion and n is an even integer number. As proof of concept, we calculate the energy of a Neel skyrmion in an ultra-thin Co/Pt cylinder, and we find that the dipolar contribution cannot be neglected and that both Dzyaloshinskii-Moriya interaction and anisotropy play an important role to stabilize the skyrmion. Additionally, we have obtained a good agreement between our analytical calculations and previously published micromagnetic simulations for n=10. For this reliable value of n, we have obtained that for a Dzyaloshinski Moriya constant D = 5.5 (mJ/m2), it is possible to stabilize a Neel skyrmion for Ku in the range 0.4 (MJ/m3) < Ku < 1.3 (MJ/m3), whereas for Ku=0.8(MJ/m3), the skyrmion stabilizes for 5.0 (mJ/m2) < D < 6.0 (mJ/m2). Thus, this analytical equation can be widely used to predict stability ranges for the Neel skyrmion in spintronic devices. © 2017 Elsevier B.V.